International trade regulation and the mitigation of climate change : World Trade Forum - Cottier, Thomas; Nartova, Olga; Bigdeli, Sadeq Z. (Cambridge books online., 2009)
How can trade regulation contribute towards ameliorating the greenhouse gas emissions and reducing their concentrations in the atmosphere?